All Days 2012
DOI: 10.2118/154233-ms
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Foamed Gas Mobility in Permeable Porous Media

Abstract: In mechanistic modeling of foam in porous media, reduced gas mobility is attributed to viscous resistance of flowing foam lamellas to gas flow, while gas trapping significantly modifies relative permeability. By using pore-network models representative of real porous media, we previously developed a relationship between flowing gas fraction and pressure gradient for strong foam (high lamella density). In this study, we expand our model to describe the effects of foam strength and pore-scale apparent gas viscos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In this regime, lamellae generation is primarily driven by snap off and leave behind mechanisms that are only poorly dependent on pressure gradient or capillary pressure. These lamellae will primarily be of the immobile variety because of the high in-situ capillary pressures demonstrated at the small pore throats and should provide a reduced but still sufficient resistance to flow [Balan et al (2012) has shown that gas relative permeability is exponentially reduced with trapped-gas saturation].…”
Section: Tested Hypothesismentioning
confidence: 99%
“…In this regime, lamellae generation is primarily driven by snap off and leave behind mechanisms that are only poorly dependent on pressure gradient or capillary pressure. These lamellae will primarily be of the immobile variety because of the high in-situ capillary pressures demonstrated at the small pore throats and should provide a reduced but still sufficient resistance to flow [Balan et al (2012) has shown that gas relative permeability is exponentially reduced with trapped-gas saturation].…”
Section: Tested Hypothesismentioning
confidence: 99%
“…In this respect, pore-scale network modeling is the main candidate and the most natural approach to accommodate such flow-structure features [19][20][21][22][23][24]. The effect of varying cross section in the flow direction can be particularly important for modeling certain flow phenomena such as extensional flows, viscoelastic effects and yield-stress dynamics which are essential for various scientific and technological purposes like enhanced oil recovery as well as many other applications [25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%